Washfastness properties of dyed pineapple leaf fibre using different dyeing techniques / Anis Nazahah Mohd Amin ... [et al.] - Mohd Amin, Anis Nazahah; Ruznan, Wan Syazehan; Ahmad Suhaimi, Suraya; Mohd Yusuf, Juliana; Ab Kadir, Muhammad Ismail; Mohd Nor, Mohd Azlin (Universiti Teknologi MARA, Negeri Sembilan, 2021)
Pineapple leaf is categorised as natural fibre resources hence creating an initiative to reduce usage of synthetic fibre. Pineapple fruits commercially have high demand in the industry causing the leaves discarded as agricultural waste. As an alternative to reduce the waste, fibres from pineapple leaf were extracted and dyed to improve the aesthetic value of pineapple leaf fibre by adding dyeing substrates using low energy consumption approach. This research is the first step towards more profound understanding on the nature of colourfastness properties pineapple leaf dyed fibre in addition on the improvement of dyeing behaviour properties. This method could further be refined by considering the production of textile materials, which can provide alternative on the usage of highly expensive silk fibres in the songket making industry. Two different methods of dyeing were used to analyse the colourfastness properties of pineapple leaf fibres. Pineapple leaf fibre was extracted using mechanical extraction. The fibres were manually extracted by water retting process and dried at room temperature prior to dyeing. Red reactive dye was applied to the pineapple leaf fibres using infrared dyeing machine and exhaustion dyeing machine. Both dyeing techniques displayed interesting colour findings, where infrared dyeing with golden shade and exhaustion dyeing with a reddish shade. Both dyeing techniques gave excellent colourfastness to washing with the moderate performance of change in colour.